Study on 10 Medicinal Plants in Sundarban Region, West Bengal, India: Study on 10 Medicinal Plants in Sundarban Region, West Bengal, India - Mukhopadhyay, Goutam (International Journal of Pharmaceutical & Biological Archive, 2018)
Modern approaches of ethnobotanical studies on various medicinal plants in Sundarban region are to create awareness among the locality along with all over India. The aim of the studies of medicinal plants will focus the cause and the help of treatment diseases. The investigation deals about 10 medicinal plants which are used by local people throughout the Sundarban region. Ethnomedicinal plants information were taken by the interview of ojha and local old villagers throughout the study period. In various villages of this region, it is found that ethnobotanical medicinal plants are used to treat common problems (such as injuries, stomachache, abdominal disorder, and skin problem). By the field visits and knowledge gather from the villagers, the study is done to motivate further research on medicinal plants which may lead to discovery of novel drugs in the fields of research and development study.